Effect of electrochemical control function on the internal structure and composition of electrodeposited polypyrrole films: A neutron reflectometry study. (1st February 2019) - Beebee, Charlotte; Watkins, Erik B.; Sapstead, Rachel M.; Ferreira, Virginia C.; Ryder, Karl S.; Smith, Emma L.; Hillman, A. Robert
Abstract: Electrodeposited conducting polymer films derived from aromatic monomers are known to possess properties that depend significantly on the deposition protocol, particularly the electrochemical control function employed. This study explores the underlying reasons for this common observation for the specific case of polypyrrole films deposited from aqueous media onto gold electrodes under potentiostatic, potentiodynamic and galvanostatic control. Although the control functions impose different conditions, the control parameters (potential, potential range and scan rate, and current) were selected so as generate films at comparable rates; this avoids inappropriate attribution of structural and compositional variations to different thickness regimes, irrespective of how they were generated. In each case, film deposition was periodically interrupted and the film characterised by specular neutron reflectivity measurements. By using d 4 -pyrrole monomer in H2 O solvent, the isotopic selectivity of neutron reflectivity was used to extract polymer and solvent concentration profiles as a function of distance from the electrode/film interface. Spatial integration of these profiles was used to quantify total film solvent populations; these are expressed as solvent volume fractions. Films grown under the three different control regimes have measurably distinct solvent volume fraction profiles and there is evolution of these profiles with increasing thickness. Ultimately, for the conditions employed, the order of increasing porosity (i.e. solvent content) by control function was potentiostatic < potentiodynamic < galvanostatic. At the end of the deposition process, the films were transferred to monomer-free electrolyte and redox cycled. This resulted in an overall increase in film solvation, but little difference in solvation with redox state (doping level). We conclude that film structure and associated solvation level do retain some memory of deposition protocol, but also respond to the medium of exposure. Graphical abstract: Image Highlights: Polymer and solvent spatial profiles within polypyrrole films have been determined using in situ specular neutron reflectivity. Growing polypyrrole films (under any given control regime) are spatially inhomogeneous composites of polymer and solvent. Growing polypyrrole films have distinct solvation profiles dictated by electrochemical control function. Subsequent redox cycling in monomer-free background electrolyte results in increased solvation. Film solvation profiles respond to environment and potential cycling, but also retain some "memory" of deposition conditions